Analisis yuridis-normatif terhadap peran dan tindakan telemarketing dalam transaksi digital - Rahmawati, Indah (Jurnal Cakrawala Hukum, 2020)
The development was needed some law in about digital regulation. At the era of industrial revolution 4.0 abandoned more conventional methods and has switched to used digital methods. The principles and values of law are indeed permanent, but if new methods are not annulled further they will cause problems in the practice of the legal world. One of many problem is telemarketing. The telemarketing method has been widely used in recent years in the economy sectoral. Marketing is indeed the spearhead of the success of a company. Problems begin to arise when telemarketing is misused by using certain gaps. This research uses a juridical-normative method with norm approach and theory analysis. The results of this study reveal that criminal prosecution will be more complex when execute with companies because the figure of a legal entity is fundamentally different from individuals in terms of accountability. In the realm of civilization many are protected by existing norms in Indonesia through financial service authority institutions and dispute resolution by the Court. Some civil problems are caused by Misbruik van Omstadigheden of the companies that manage financial services. How to cite item:Â Rahmawati, I. (2020). Analisis yuridis-normatif terhadap peran dan tindakan telemarketing dalam transaksi digital.Â Jurnal Cakrawala Hukum, 11(1), 60-70. doi:https://doi.org/10.26905/idjch.v11i1.4047